Resistance to interprofessional collaboration in in-service training in primary health care* - Lago, Luana Pinho de Mesquita; Dóbie, Daniel Vannucci; Fortun, Cinira Magali; L’Abbate, Solange; Silva, Jaqueline Alcântara Marcelino da; Matumoto, Silvia (Revista da Escola de Enfermagem da USP, 2022)
Objective: to analyze the resistance to interprofessional collaboration in the professional practices of residents in primary health care. Method: Social and clinical qualitative research with 32 residents of a Multiprofessional Residency, carried out from 2017 to 2018. Data production included Institutional Analysis of Professional Practices, document analysis; investigator’s diary; and observation. Data were analyzed based on Institutional Analysis concepts. Results: There were contradictions between the reproduction of uniprofessional education with a focus on the specialty and interprofessional collaborative practices. The resistance analysis pointed to two axes: not-knowing as an analyzer of resistance to collaboration; interprofessional interference and knowledge-power relations. Residents’ practices were characterized as resistant to interprofessional collaboration. Conclusion: The resistance analysis in the Multiprofessional Residency showed integrative movements of assimilation and disputes with physician-centered power, with damage to the sharing of care and interprofessional communication. The collective analysis questioned health professionals education, revisiting the perspective of comprehensive care guided by the users’ needs.